PENERAPAN MODEL PEMBELAJARAN PREDICT- OBSERVE-EXPLAIN (POE) UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA MATERI SISTEM ORGAN MANUSIA SISWA KELAS V SDN 188 PEKANBARU - Dwi Ramadanti; Jaya Adi Putra, M.; Munjiatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the improvement of science learning outcomes concerning human organ systems among fifth-grade students in an elementary school in Pekanbaru through the implementation of the Predict-Observe-Explain (POE) learning model. The research was prompted by suboptimal student performance resulting from teacher-centered instruction and a lack of active engagement in abstract science concepts. A quantitative approach was adopted using an experimental method with a Posttest-Only Design with Nonequivalent Groups. The research subjects consisted of an experimental class implementing the POE model and a control class utilizing conventional learning. Data were collected through learning outcome tests and analyzed using normality, homogeneity, and independent sample t-tests. The results demonstrated a significant difference in learning outcomes between the two groups, with a significance value of 0.002 (p < 0.05). Consequently, it is concluded that the Predict-Observe-Explain (POE) model has a positive effect on enhancing science learning outcomes regarding human organ systems in elementary education.